Understanding university students’ affect in interactions with quantum physics - Anttila, Daria (fi=Turun yliopisto|en=University of Turku|, 2025)
The second generation of quantum applications, like quantum computers and sensors, have emerged, and quantum physics has found its way to social media, films, news and TV. Educating the general public and the future quantum workforce with quantum mechanics basics is crucial. An excessive amount of literature has been produced in the field of quantum physics education exploring students’ difficulties in learning quantum physics and presenting new teaching approaches, tools and materials. However, students’ relation to quantum physics and experiences in studying it remained unexplored. To develop quantum physics education further we need to understand our students and hear their voices. In this thesis, I focus on university students and investigate the five components of student affect in relation to studying quantum physics: interest, self-efficacy beliefs, motivation, emotions, and attitudes. Through questionnaires, I collected information about STEM (science, technology, engineering and mathematics) and non-STEM university students’ encounters with quantum physics and interest to study it, investigated the potential of a one-day event to trigger interest in quantum physics among physics and mathematics university students, and followed affective experiences of physics students during an obligatory quantum mechanics course. The results showed that students have significant differences in their affective experiences. The common factor among both STEM and non-STEM students is an interest in quantum physics topics, which can be utilized as a good momentum for teaching and outreach. However, another common factor was found: the view that quantum physics is relevant for the future of society but irrelevant for students’ own studies and future career. With my research, I open a discussion on university students’ affective experiences in interactions with quantum physics. My findings can be implemented in teaching design to maintain students’ motivation and interest in quantum physics and enhance learning engagement. Future research could explore the underlying reasons behind students’ emotions and attitudes toward quantum physics studying and give more insight into students’ affective experiences.